Antibacterial and Antioxidant Efficacies of Secondary Metabolites from the Roots of Cyphostemma adenocaule: A Combined In Vitro and In Silico Study - Hadush Gebrehiwot; Yadessa Melaku; Muhdin Aliye; Urgessa Ensermu; Aman Dekebo; Milkyas Endale; Daniel Rentsch; Mo Hunsen (Journal of Tropical Medicine)
Cyphostemma adenocaule is a therapeutic plant traditionally used to treat rabies, snake bite, diarrhea, and wound healing. To address the bioactive compounds exhibiting these activities, we performed a comprehensive study on the roots of the plant. Thus, the present study aims to inspect the in vitro antioxidant and antibacterial efficacies of compounds isolated from the combined dichloromethane : methanol (1 : 1) and methanol extracts of C. adenocaule along with the in silico study of their interaction with selected protein targets. The silica gel column chromatography technique was used for the isolation of compounds, and the antibacterial and antioxidant activities were evaluated using agar disc diffusion and DPPH radical scavenging assays, respectively. Furthermore, in silico molecular docking screening, pharmacokinetics, and toxicity protocols of the compound isolates were performed to offer the potential applications of the compounds in developing novel medications. A BIOVIA Discovery Studio in combination with AutoDock Vina 4.2 software, SwissADME, and ProTox-II prediction web tools were used to generate the molecular docking, pharmacokinetics, and toxicity profiles, respectively. Notably, the chromatographic separation of the combined extracts yielded six known compounds, namely, β-sitosterol (1), 3-hydroxyisoagatholactone (2), ε-viniferin (3), myricetin (4), tricuspidatol A (5), and parthenocissin A (6). The in vitro antibacterial activities revealed the highest inhibition zone by tricuspidatol A (5) (16.67 ± 0.47), showcasing its potent activity against S. aureus at 2 mg/mL, compared to ciprofloxacin (21.50 ± 0.41). ε-Viniferin (3) (IC50: 0.32 μg/mL) exhibited greater antioxidant activity than the others and displayed promising results compared to ascorbic acid (0.075 μg/mL). The molecular docking study revealed the highest binding affinity by ε-viniferin (3) (−9.9 kcal/mol) against topoisomerase II α. 3-Hydroxyisoagatholactone (2) and ε-viniferin (3) fulfilled Lipinski’s rule with no violation, and the organ toxicity predictions revealed that all the compounds showed no cytotoxicity and hepatotoxicity effects. Thus, this study’s combined in vitro and in silico outcomes suggest the potential use of the isolated compounds in drug discovery and support the traditional relevance of C. adenocaule.